Satisfaction with Active Learning Activities Implementation in Digital, Media, and Information Literacy: A Case Study of Kamphaeng Phet Rajabhat University - Chongchorhor, Chokthamrong; Pathumpong, Nujarin (Journal of Information Technology and Innovation, 2023)
The purpose of this study was to examine subject satisfaction with active learning activities. 91 students are enrolled in "Digital, Information, and Media literacy (9001301)" for the first semester of the academic year 2022 at Kamphaeng Phet Rajabhat University’s Bachelor of Business Administration Course. The instruments of research were questionnaires. The study used frequency distribution, percentage, mean, and standard deviation statistics. Students reported overall satisfaction with "teaching preparation," "teaching technique," "material received," and "active learning activities for each category," according to the findings. There are recommendations for future enhancements, including the addition of more study time. Modernizing equipment via upgrades. For the next academic year, let’s keep students engaged in interesting active learning activities like moral theatre plays on digital society’s issues, news analyses and presentations about Thailand’s cyber criminals.